2020
DOI: 10.3390/su12051916
|View full text |Cite
|
Sign up to set email alerts
|

A Benefit–Cost Analysis of Food and Biodegradable Waste Treatment Alternatives: The Case of Oita City, Japan

Abstract: As the generation of food scrap, kitchen, and biodegradable wastes increases, the proper handling of these wastes is becoming an increasingly significant concern for most cities in Japan. A substantial fraction of food and biodegradable waste (FBW) ends up in the incinerator. Therefore, an analytic hierarchy process (AHP) benefit–cost analysis technique was employed in this study to compare different FBW treatment technologies and select the most appropriate FBW disposal technology for Oita City. The four FBW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…There should also be subsidies for their operation, such as FIT schemes (despite the difficult situation they face for power grid use). The effects of BGPs on the environment and dairy farming have already been explained in previous studies, as mentioned above [1,3,5,6,[9][10][11][12][13][14][15]. Therefore, it should be emphasized that BGPs are different from other power sources that require policy design, such as preferential grid use and support of continuous FIT schemes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There should also be subsidies for their operation, such as FIT schemes (despite the difficult situation they face for power grid use). The effects of BGPs on the environment and dairy farming have already been explained in previous studies, as mentioned above [1,3,5,6,[9][10][11][12][13][14][15]. Therefore, it should be emphasized that BGPs are different from other power sources that require policy design, such as preferential grid use and support of continuous FIT schemes.…”
Section: Discussionmentioning
confidence: 93%
“…The biogas produced from BGPs is also important. ADs in BGPs use organic waste effectively to produce renewable energy that is distributed and can increase self-sufficiency and mitigate climate change [14,15,28]. Distributed, self-sufficient energy is important in Japan given its history of large earthquakes (e.g., the 2011 Great East Japan Earthquake and the 2018 Hokkaido Eastern Iburi Earthquake) that have cut off the supply of large-scale, centralized power plants [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paratosh et al (2017), revealed that conversion of food waste into energy via anaerobic processes in terms of methane is economically worthwhile. According to Babalola (2020), the most appropriate alternative aimed at handling food waste is anaerobic digestion followed by composting. Incineration turn out to be the third most suitable alternative in terms of the overall results, while landfilling is presumed to be the worst case because of the substantial costs and low benefits.…”
Section: Food Waste Generation Rate As a Candidate For Energy Recovery Via Bio-digestionmentioning
confidence: 99%
“…AD is a process, which involves the breaking down of biodegradable organic matter by the action of bacteria in the absence of oxygen. AD technology has become an attractive and preferred technology around the world through the waste-to-energy option to deal with the ever increasing amount of waste generated [3,4,5]. In the production of biogas the AD process is carried out in a reactor, which is a sealed vessel whose design and construction is dictated by the specific site conditions and feedstock.…”
Section: Introductionmentioning
confidence: 99%